The impact of guar gum biopolymer on mechanical characteristics of soil reinforced with palm fiber - Arabani, Mahyar; Shalchian, Mohammad Mahdi; Haghsheno, Hamed (Bulletin of engineering geology and the environment, 2025)
Incorporating sustainable stabilizers into the geo-ecosystem is an effective approach to improving the mechanical properties of the soil while addressing ecological issues. The main objective and novelty of this study are to assess the combined use of palm fiber and guar gum in soil stabilization, estimate their behavior in practices, outline their obstacles and potential for soil improvement, and consider their ecological effects. For this purpose, four different dosages of guar gum (0.5, 1, 1.5, and 2%) and three ratios of palm fiber (0.2, 0.4, and 0.6%) in lengths (5, 10, and 15 mm) were considered. Laboratory tests conducted for this purpose include compaction, compressive, shear, and tensile strength, California bearing ratio (CBR), and microstructure analysis. Initially, the optimal dosage of guar gum was determined through the unconfined compressive test. Subsequently, the impact of optimal guar gum and palm strands on the mechanical characteristics of treated soil was examined. The results revealed that compressive and shear strengths of stabilized and reinforced soil improved by 200% and 71%, respectively, compared to the control samples. Also, increasing the palm dosage improved the failure strain by up to 11.4%, cohesion enhancement by up to 96 kPa, and soil brittleness reduction by 13.5%. The tensile and CBR test results demonstrated that incorporating fiber into the soil increased its tensile strength and CBR by 32.5 kPa and 31.16, respectively. A microstructure study revealed that adding guar gum to the fiber composite improved the interlocking between clay particles and fibers by generating a hydrogel.